Redox signaling during hypoxia in mammalian cells - Kimberly A. Smith; Gregory B. Waypa; Paul T. Schumacker (Redox Biology, 2017)
Hypoxia triggers a wide range of protective responses in mammalian cells, which are mediated through transcriptional and post-translational mechanisms. Redox signaling in cells by reactive oxygen species (ROS) such as hydrogen peroxide (H2O2) occurs through the reversible oxidation of cysteine thiol groups, resulting in structural modifications that can change protein function profoundly. Mitochondria are an important source of ROS generation, and studies reveal that superoxide generation by the electron transport chain increases during hypoxia. Other sources of ROS, such as the NAD(P)H oxidases, may also generate oxidant signals in hypoxia. This review considers the growing body of work indicating that increased ROS signals during hypoxia are responsible for regulating the activation of protective mechanisms in diverse cell types.